An Analysis of Questioning Skill in Elementary School Pre-service Teachers Based on Bloom's Taxonomy. Issue 1 (February 2021) - Rahmatih, A N; Indraswati, D; Gunawan, G; Widodo, A; Maulyda, M A; Erfan, M
Abstract: Questioning is an important skill for students which reflects their critical thinking skills. It is also an indicator of creative thinking and even metacognition abilities. This study used Bloom's Taxonomy to analyze students' questioning skills. The purpose of this study was to look at the level of student questioning skills based on Bloom's Taxonomy criteria. The number of questions classified in the factual category was 50% of the 114 questions made. Questions included in the conceptual category were 35%, the procedural category was 5%, while questions included in the metacognitive category were 10%. The conclusions are: (1) The quality of questions made by PGSD students is mostly in the factual cognitive category that requires answers with a low cognitive level; (2) Most questions are at the cognitive level of analyzing; (3) the ability of the research subject in converting information to questions is still at the basic level and the initial skills of HOTS (Higher Order Thinking Skills).